2012
DOI: 10.1177/1077559512436674
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ Attitudes Toward Evidence-Based Practices and Implementation of Parent–Child Interaction Therapy

Abstract: Child abuse and neglect affects many families each year, but evidence-based parent training programs can be instrumental in reducing maltreatment. Parent-Child Interaction Therapy, a parent training program developed for treatment of disruptive child behavior, has demonstrated effectiveness with families at risk of or exposed to child maltreatment. However, methods for disseminating this evidence-based intervention in community settings are not well understood. This study examined the association between commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
(47 reference statements)
2
36
0
1
Order By: Relevance
“…Another attitudinal factor, attitudes toward EBTs, has received mixed results. Shapiro et al (2012), for example, found that these attitudes did not predict intervention use following training, but Nelson et al (2012) found that more positive attitudes did predict increased participation in post-training consultation activities. In terms of more practical considerations, Aarons et al (2009) found that stakeholders listed the potential for EBT training to count toward clinicians' licensure and continuing education credits as an advantage of implementing such treatments, suggesting that this may serve as a facilitator.…”
Section: Identification Of Facilitators and Barriers To Ongoing Trainingmentioning
confidence: 95%
See 4 more Smart Citations
“…Another attitudinal factor, attitudes toward EBTs, has received mixed results. Shapiro et al (2012), for example, found that these attitudes did not predict intervention use following training, but Nelson et al (2012) found that more positive attitudes did predict increased participation in post-training consultation activities. In terms of more practical considerations, Aarons et al (2009) found that stakeholders listed the potential for EBT training to count toward clinicians' licensure and continuing education credits as an advantage of implementing such treatments, suggesting that this may serve as a facilitator.…”
Section: Identification Of Facilitators and Barriers To Ongoing Trainingmentioning
confidence: 95%
“…Furthermore, with the exception of Nelson et al (2012) and Fritz et al (2013), few have examined the impact of barriers and facilitators on providers' participation in monitoring activities, which are important in supporting fidelity. The current study addressed these areas by utilizing objective measures of participation in post-workshop training activities aimed at assisting with and monitoring implementation among clinicians who treat children exposed to trauma.…”
Section: Limits Of Previous Researchmentioning
confidence: 98%
See 3 more Smart Citations